The mode functional is not elicitable - Heinrich, Claudio (Biometrika, 2014)
SUMMARY. This article is concerned with point forecasting of a real-valued random variable with a general Lebesgue density. Answering a question of Gneiting 2
Published: 28 November 2013
Gesehen am 21.09.2020